2014
DOI: 10.1002/erv.2323
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Bad Posing as a Model: An Objective Manner of Study Upward Own‐Body Comparisons in Body‐Dissatisfied Women

Abstract: Emotional effects of upward body comparisons are suggested to occur automatically. A startle reflex paradigm was used to objectively examine the emotions elicited by viewing a picture of one's own body adopting a model pose or a neutral pose, in 30 women with high body dissatisfaction (HBD) and 33 women with low body dissatisfaction (LBD). In-task emotional responses in perceived valence, arousal and control were assessed. Additionally, post-task positive/negative and body-related beauty feelings were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…The decision to make the participants hold the posture only before the ME (not during) and for a short period of time (2 minutes) is based on the study by Carney et al [ 20 ] and the conclusions of the review by Carney et al [ 39 ], that suggested that the length of time that the posture is adopted should be carefully considered because it seems to be an important moderator variable responsible for the contradictory results found in the effects of posture (e.g., holding some postures for a long time might cause discomfort or habituation). In addition, Ortega-Roldán et al [ 40 ] found that women with high body dissatisfaction (compared to women with low body dissatisfaction) that were exposed to photographs of their own body in model postures (upright position with one hand on the waist and the other extended, and one knee slightly flexed) compared to neutral postures (upright position with arms extended and close to the trunk) showed less pleasure, more negative and ugliness feelings, and an increased startle response (a reflex that is potentiated when processing stimuli associated with negative affect). Moreover, the decision to manipulate the women’s backs as well as to expand the body, is based on the positive results that the upright postures have shown (e.g., [ 22 , 23 ]).…”
Section: Measures and Materialsmentioning
confidence: 99%
“…The decision to make the participants hold the posture only before the ME (not during) and for a short period of time (2 minutes) is based on the study by Carney et al [ 20 ] and the conclusions of the review by Carney et al [ 39 ], that suggested that the length of time that the posture is adopted should be carefully considered because it seems to be an important moderator variable responsible for the contradictory results found in the effects of posture (e.g., holding some postures for a long time might cause discomfort or habituation). In addition, Ortega-Roldán et al [ 40 ] found that women with high body dissatisfaction (compared to women with low body dissatisfaction) that were exposed to photographs of their own body in model postures (upright position with one hand on the waist and the other extended, and one knee slightly flexed) compared to neutral postures (upright position with arms extended and close to the trunk) showed less pleasure, more negative and ugliness feelings, and an increased startle response (a reflex that is potentiated when processing stimuli associated with negative affect). Moreover, the decision to manipulate the women’s backs as well as to expand the body, is based on the positive results that the upright postures have shown (e.g., [ 22 , 23 ]).…”
Section: Measures and Materialsmentioning
confidence: 99%